Mary Anne and the secret in the attic - Martin, Ann M., 1955- (New York : Scholastic Books, 1992)
Mary Anne's father never talks about her mom, who died when she was a baby, so she goes up to the attic and looks for anything she can find that will tell her more about her mother.
5.9
3-6
Keywords: Fathers and daughters -- Fiction; Mothers and daughters -- Fiction; Mystery and detective stories; Father-daughter relationship -- Fiction; Mother-daughter relationship -- Fiction; Mystery fiction